The impact of internal stratifications on the performance of oil and gas pipes. (February 2021) - Kantyukov, Rafael; Ryakhovskikh, Ilya; Kashkovskiy, Roman
Graphical abstract: Highlights: The operability of the pipes containing internal stratifications was investigated. The properties of steel near the stratifications are consistent with the required performance. Delamination of steel of certain sizes does not significantly affect the performance of pipes. Abstract: The work investigated pipes of the main gas pipeline with a service life of more than 45 years. Initially, this gas pipeline was designed for the technological purposes. It was intended to remove associated gases generated during the purification of methane from acidic impurities, but subsequently, as production was modernized, it was transferred to purified natural gas transport. Nevertheless, the presence of corrosive components in the transported gas during the initial period of operation of the gas pipeline led to the appearance of structural defects in the form of delamination in the pipe wall. The purpose of the study was to evaluate the performance of defective pipes based on a set of laboratory and bench tests. During the construction of the pipeline, imported longitudinal welded pipes made from steel of strength class X53 and X56 were used. The study of the chemical composition and mechanical properties of pipe steel did not reveal significant deviations of these characteristics from normalized values. It was noted that the content of non-metallic inclusions was high, but acceptable for pipes Ø 1020 mm. Based on an analysis of the modes of gas transport through the gas pipeline over the past 10 years, a model of its operation has been formed, which includes alternately repeating combinations of amplitude and pulsation loading cycles. To carry out life tests, a research stand was constructed containing pipe fragments with extended zones of internal stratifications. Test results showed that delamination up to 1.5 m 2 in size and/or up-to 3.5 m in length, as an independent type of defects, do not significantly affect the performance of the pipes.